The skyline operator algorithms: a review - Mohd Rum, Siti Nurulain; Mohd Ariffin, Noor Afiza; Asmawi, Aziah; Mohd Rum, Siti Fatimah; Dzolkhifli, Zarina (Science and Engineering Research Support Society, 2019)
In the present decade, there is the revival of interest to find the best way to query the database that able to provide not only a single answer, but also a set of answers that can be the most preferred by users .In many cases, the overflow of data generated from social media, and many other data stored and shared over the Internet makes the data access becoming near –infinite to the users. This has led to the need of intuitive formulation that able to provide the best choices from every unconceivable situation .Recently, the skyline computation has gained a lot of attention in the database research community for advanced queries semantic.The skyline query is introduced to be the syntax extension in SQL query to support multi-criteria data selection involving advanced queries. This paper surveys the techniques employed in initial algorithms of the skyline query processing .Some trade-offs about those different approaches are also identified throughout this study .